The effects of procedural injustice during police–citizen encounters: a factorial vignette study - Reisig, Michael Dean (Journal of experimental criminology, 2018)
This study tested the effect of procedural injustice relative to being sanctioned by police on a variety of outcome measures, such as decision acceptance and immediate compliance, in two types of police-citizen encounters, traffic stops and noise complaints.